An integrative review of literature: virtual exchange models, learning outcomes, and programmatic insights - Anna Zak (University of Groningen Press, 2021)
This integrative review explores English language publications to determine trends present in Virtual Exchange (VE) research over a span of ten years. The review presents a brief introduction to VE, highlights key scholars in the field, and describes various VE models. In addition, learning outcomes and programmatic insights present in current scholarship are categorized and examined. This review can serve as a helpful tool for practitioners new to VE, as well as for scholars interested in expanding the VE research field.